PROFESSIONAL MOBILITY OF A FUTURE SPECIALIST IN THE STRUCTURE OF READINESS FOR ACTIVITY IN SPECIALTY: ESSENTIAL AND CONCEPTUAL ASPECT - Олександр Діденко; Андрій Балендр; Вадим Рижиков; Тетяна Новікова; Ольга Туз (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2021)
The article presents an analysis and generalization of approaches to the essence and content of professional mobility of future specialists. It is concluded that professional mobility is directly interrelated with readiness to work in the specialty, since these two concepts have common elements in the structure, in particular professional knowledge, abilities, skills and professionally important qualities. Taking into account the results of the analysis of research related to the problem of professional mobility, it was found out that this concept can be defined as readiness and ability to work in the context of transformation of professional (production, service) tasks, development of new specialties or changing them. Professional mobility covers the ability to successfully switch to another activity or change types of activities, effectively use the system of generalized professional techniques to perform any tasks in the professional sphere, and it is relatively easy to move from one type of activity to another. For professional mobility, it is important to have a high level of generalized professional knowledge, experience in improving them and obtaining them independently. The results of the review of publications on the research topic suggest that there are two types of mobility - horizontal and vertical. Horizontal mobility involves the transition of an individual or social object from one social position to another, which is at the same level, as well as a change of place of residence. As for vertical mobility, it involves the transition of an individual or social object from one social position to another. It was found out that mobility is an integrative property that is formed and developed during practical, educational, social, socio-cultural activities of a person and provides him or her with the opportunity to realize one's inclinations, abilities, opportunities.